Frontispiece: Achieving High 1H Nuclear Hyperpolarization Levels with Long Lifetimes in a Range of Tuberculosis Drug Scaffolds. Issue 67 (1st December 2017) - Norcott, Philip; Rayner, Peter J.; Green, Gary G. R.; Duckett, Simon B.
Abstract : The nuclear magnetic resonance (NMR) detectability of several TB‐relevant agents have been significantly improved through the use of the parahydrogen‐based hyperpolarization protocol signal amplification by reversible exchange (SABRE) in conjunction with the 2 H‐labelling of key sites within their molecular structures and the 2 H‐labelling of the magnetization‐transfer catalyst. The T 1 relaxation times and polarization levels of these agents are quantified under test conditions to produce a protocol to identify structurally optimized motifs for future detection in MRI. For more information see the Full Paper by S. B. Duckett et al. onpage 16990 ff.